2011
DOI: 10.1080/00036840802600566
|View full text |Cite
|
Sign up to set email alerts
|

Size, innovation and internationalization: a survival analysis of Italian firms

Abstract: Firms' survival is often seen as crucial for economic growth and competitiveness. This article focuses on business demography of Italian firms, using an original database, obtained by matching and merging to gain the intersection of three firm level datasets. This database allows us to simultaneously consider the effect of size, technology, trade, FDIs and innovation on firms' survival probability. We show that size and technological level positively affect the likelihood of survival. Internationalized firms s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 23 publications
8
53
0
12
Order By: Relevance
“…Compared to profitability and growth, very few studies have examined the implications of new venture internationalization on survival. A few of the notable exceptions include the study by Lee et al (2012) of Korean small-and medium-sized firms and the study by Giovannetti et al (2011) of Italian firms, which ironically concluded positive and negative results, respectively. Another study by Coeurderoy et al (2012) found a positive, linear relationship between new venture internationalization and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to profitability and growth, very few studies have examined the implications of new venture internationalization on survival. A few of the notable exceptions include the study by Lee et al (2012) of Korean small-and medium-sized firms and the study by Giovannetti et al (2011) of Italian firms, which ironically concluded positive and negative results, respectively. Another study by Coeurderoy et al (2012) found a positive, linear relationship between new venture internationalization and survival.…”
Section: Introductionmentioning
confidence: 99%
“…The variables were measured in the pretreatment year. Significance levels: ***< 0.001; **< 0.010; *< 0.050. with more innovative counterparts might offer the highest returns (for more evidence on this category of firms in the case of Italy, see Benfratello, Schiantarelli, & Sembenelli, 2008;and Giovannetti, Ricchiuti, & Velucchi, 2011). Firms active in low-tech sectors can expand both their investments and employment with no immediate tradeoff between capital deepening and employment levels.…”
Section: Heterogeneity At the Thresholdmentioning
confidence: 99%
“…One interpretation of these findings is that exporting firms were more adversely affected by the global economic slowdown, given sluggish demand for Vietnamese exports among trading partners 12 . This negative relationship between exports and firm survival, however, has been found elsewhere, possibly because of competitive pressures in international markets (Giovannetti et al 2011;Lopez 2006), while the positive relationship between imports and survival is well established in the empirical literature based primarily on the experience of Organization of Economic Development and Cooperation countries (Wagner 2012). In any event, this finding raises questions about the view that institutionally determined barriers to entry for SMEs in accessing export markets generate large efficiency costs by precipitating the demise of potentially profitable exporting SMEs.…”
Section: Notementioning
confidence: 95%